2020
DOI: 10.1007/s40843-019-1255-4
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian optimization based on a unified figure of merit for accelerated materials screening: A case study of halide perovskites

Abstract: The figure of merit is of crucial importance in materials design to search for candidates with optimal functionality. In the field of photovoltaics, the bandgap (E g ) is a well-recognized figure of merit for screening solar cell absorbers subject to the Shockley-Queisser limit. In this paper, the bandgap as the figure of merit is challenged since an ideal solar cell absorber requires multiple criteria such as stability, optical absorption, and carrier lifetime. Multiple criteria make the quantitative descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…In this paper we have tried to explore the experimentally synthesized small band gap halide double perovskites Cs2CuMCl6 (M=Sb, Bi) [22][23][24][25][26][27][28][29][30]. The nanocrystals of these halide doubled perovskites and other related materials have been experimentally reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we have tried to explore the experimentally synthesized small band gap halide double perovskites Cs2CuMCl6 (M=Sb, Bi) [22][23][24][25][26][27][28][29][30]. The nanocrystals of these halide doubled perovskites and other related materials have been experimentally reported.…”
Section: Introductionmentioning
confidence: 99%
“…12 In this regard, doubleperovskites such as Rb 2 NaGaBr 6 and Rb 2 KGaBr 6 have the potential to replace CH 3 NH 3 PbI 3 solar absorber material as they have direct band gaps in the required range. 18 This is further strengthened by the fact that Cs 2 AgBiX 6 , a lead-free and chemically stable halide double perovskite, has recently been shown to be an environment-friendly alternative to CH 3 NH 3 PbI 3 . 19 Since Rb 2 NaGaBr 6 and Rb 2 KGaBr 6 have only recently been examined in theoretical studies, not enough information about their electronic structure and optical properties is available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…19 Since Rb 2 NaGaBr 6 and Rb 2 KGaBr 6 have only recently been examined in theoretical studies, not enough information about their electronic structure and optical properties is available in the literature. 18,20 In addition to their potential for photovoltaic applications, Wang et al 21 have also proposed double perovskite Cs 2 AgBiBr 6 for photocatalytic hydrogen production in combination with reduced graphene oxide. It has been shown that the prepared material exhibits high stability for over 120 hours.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations